Self-Esteem Among Children Of Working And Non-Working Mothers: A Review And Conceptual Analysis - Ghosh, Sheena Misra; Singh, Reena (Journal of Neonatal Surgery, 2025)
Self-esteem is a fundamental psychological construct that significantly influences children’s emotional, social, and behavioural development. In the context of rapidly changing family structures and evolving parental roles, maternal employment has emerged as an important factor shaping children’s self-perception. The differing roles of working and non-working mothers create distinct developmental environments, raising important questions regarding their influence on children’s self-esteem. While working mothers may foster independence and adaptability, non-working mothers may provide greater emotional availability and consistent supervision, both of which contribute differently to a child’s sense of self-worth. This paper presents a comprehensive review of existing literature on self-esteem among children of working and non-working mothers. It critically examines prior research to understand the nature of this relationship and to identify key factors influencing self-esteem, including parenting style, maternal involvement, socio-economic conditions, and the quality of parent–child interaction. The review highlights that the impact of maternal employment on self-esteem is complex and cannot be understood in isolation, as multiple interrelated factors contribute to children’s psychological development. The literature suggests that maternal employment status alone is not a decisive determinant of children’s self-esteem. Rather, the quality of emotional support, parenting practices, and the broader socio-cultural environment play a more significant role. The paper also identifies gaps in existing research, particularly in terms of integrated and context-specific analyses, and emphasizes the need for a balanced and holistic understanding of child development